Experimental, theoretical and numerical study on the shear stress of adhesive layer in FRP-bamboo scrimber composite beams - Yongchao Zhang; Man Liu; Caimei Liu; Xizhi Wu; Yutong Li; Xianjun Li; Zhangjing Chen (Sustainable Structures, 2024)
The adhesive layer is an important factor affecting the mechanical properties of FRP- bamboo scrimber composite beams (FBSCB). However, studies on the interfacial shear stresses in the adhesive layers with both ends of FRP and bamboo scrimber beam aligned have been rarely reported. To this end, a two-parameter theoretical calculation model and a finite element model (FEM) based on cohesive zone model were hereby established to solve for the adhesive layer interface shear stresses, which was verified by four-point bending experiments. The results show that both the two-parameter theoretical model and the FEM can effectively compute the shear stress of the adhesive layer. Meanwhile, the FEM simulation results not only reflect the detailed changes of the shear stress, but also provide a better analysis of the shear stress at the adhesive layer with a small fluctuation range. There are three zones of shear stress at the adhesive layer of FBSCB under four-point bending load, i.e., the bending and shearing zone, the transition zone and the pure bending zone. In the bending and shearing zone, the shear stress of the adhesive layer interface increases 2.61 times and 2.5 times, respectively when the thickness and elastic modulus of FRP increase three times. However, the stress remains constant at zero in the pure bending zone.